Method for preparing copper-based nanoparticle / attapulgite composite antibacterial material from red peony root extract
The preparation of copper-based nanoparticles/concave-concave-concave-rodite composite materials by hydrothermal method of red peony extract was solved, and the problem of complex and low efficiency of copper-based nanomaterial preparation process in the prior art was solved, and the efficient preparation of nanocomposites with strong antibacterial activity was achieved. Material, suitable for fighting drug-resistant bacteria.
Patent Information
- Application Number
- CN202411423119.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-03
AI Technical Summary
The preparation process of existing copper-based nanomaterials is complicated and inefficient, and it is difficult to control the scale and morphology of nanoparticles, which cannot effectively solve the problem of bacterial resistance.
Copper-based nanoparticles/concave-concave-rodite composite materials were prepared by hydrothermal method using red peony extract, and nanoparticles were used to promote the formation of nanoparticles, and the pH adjustment was used to obtain the load of highly active copper and copper oxide nanoparticles. Concave and concave rock stone composite material.
It has achieved efficient preparation of copper-based nanoparticles/concave-concave-concave-rodite composite materials, with excellent antibacterial activity, photocatalytic and photothermal bactericidal properties, and has strong bactericidal ability to drug-resistant bacteria, and the preparation process is clean and environmentally friendly.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano material preparation technology and biomedical application, and specifically relates to a method for preparing a copper-based nano particle / attapulgite composite antibacterial material by utilizing red peony root extract. Background Art
[0002] Copper is highly safe to use and has a wide range of applications in biomedicine and medical devices. In recent years, with the development of nanotechnology, copper-based nanomaterials with enhanced antibacterial properties have received great attention. At present, the problem of bacterial resistance has become increasingly prominent. The development of new antibacterial materials has become an important strategy to deal with drug-resistant bacteria. Nanomaterials with high antibacterial properties have become one of the breakthroughs (Progress in Chemistry, 2022, 34(11): 2540-2560.). In addition to the intrinsic antibacterial activity, copper-based nanomaterials (such as copper nanoparticles and cuprous oxide nanoparticles, etc.) can effectively convert the energy of near-infrared light into heat energy through localized surface plasmon resonance absorption of near-infrared light, thereby achieving local sterilization or targeted photothermal therapy (Micro-Nano Electronic Technology, 2023, 60(11): 1801-1807.). In addition, cuprous oxide has a narrow bandgap (~2.0 eV) and can be excited by visible light, which has the potential for photocatalytic sterilization (Journal of Inorganic Chemistry, 2019, 35(03): 459-466.). However, the reported preparation process of copper-based nanomaterials is cumbersome, complex and inefficient, and needs to be further enhanced and improved.
[0003] Biosynthesis is a green method for preparing metals and metal oxides that has attracted much attention in recent years. Studies have shown that plant-mediated biosynthesis is not only clean and environmentally friendly, but also simple to operate and easy to scale up. However, the size and morphology of nanoparticles produced by conventional plant-mediated green synthesis methods are difficult to control (Green Chemistry Letters and Reviews, 2022, 15(1): 187–215). Hydrothermal synthesis is a common technology for producing metal-based nanomaterials. It has high synthesis efficiency and wide applicability. The products obtained have advantages such as uniform phase, high purity, good crystallinity and high yield. Combining plant-mediated green technology with hydrothermal technology will hopefully enable the efficient synthesis of highly active copper-based nanoparticles. Red peony root is a commonly used Chinese herbal medicine in clinical practice. The main components of red peony root extract are phenolic substances such as paeoniflorin and oxidized paeoniflorin, which have excellent antioxidant properties, can promote the formation of nanoparticles, and are expected to give nanoparticles better biological activity.
[0004] In addition, the regulation of size and dispersibility is one of the technical limitations of preparing highly active and stable metal oxide nanoparticles (Nano-micro Letters, 2022, 14(1): 171.). Studies have shown that introducing carriers to regulate crystal growth is one of the important strategies to control the aggregation and growth of small-scale nanoparticles (Small, 2022, 18(16): e2107401.). Attapulgite is a natural one-dimensional nanomaterial with rich pore structure and surface silanol groups. It can bind to highly active crystal nuclei through hydrogen bonding to prevent particle aggregation and growth from physical space (Chemical Record, 2018, 18(7-8): 1125-37. Journal of the Chinese Ceramic Society, 2024, 52(01): 359-370.). At the same time, nanoparticles loaded on attapulgite rod crystals will have higher stability and can achieve a more lasting antibacterial effect. At present, there is no report on the construction of attapulgite-copper-based nanocomposites using plant-mediated hydrothermal method. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a copper-based nanoparticle / attapulgite composite antibacterial material using a red peony root extract, which makes full use of the rich phenolic and other active substances in the Chinese medicinal material red peony root to achieve a one-step hydrothermal synthesis of a copper-based nanoparticle / attapulgite nanocomposite material. The preparation process is clean and environmentally friendly, the composite material structure is stable, the copper-based nanoparticle loading rate is high, and the product performance is excellent.
[0006] 1. Preparation and characterization of copper-based nanoparticles / attapulgite composite antibacterial materials The invention provides a method for preparing a copper-based nanoparticle / attapulgite composite antibacterial material by using a red peony root extract. The method comprises the following steps: grinding the red peony root through a 200-mesh sieve, adding the crushed red peony root into deionized water, soaking the crushed red peony root in a water bath at 50-70°C for extraction for 0.5-2h, and centrifuging to obtain a red peony root extract; dispersing the attapulgite in the red peony root extract under stirring conditions, adding copper salt and stirring at room temperature for 2-5h, adjusting the pH value, transferring the mixture into a reaction kettle, performing a hydrothermal reaction at 80-180°C for 0.5-10h, naturally cooling the mixture, centrifuging the product, washing it three times with deionized water, and vacuum drying the product to obtain the copper-based nanoparticle-attapulgite nanocomposite antibacterial material.
[0007] The solid-liquid ratio (g / mL) of the red peony root to deionized water is 1:3-1:30. The solid-liquid ratio (g / mL) of the attapulgite to the red peony root extract is 1:10-1:100.
[0008] The copper salt is at least one of copper acetate, copper nitrate and copper chloride, and the copper ion concentration in the reaction system is 0.01-1 mol / L. The pH adjuster is 0.5-5 mol / L sodium hydroxide, and the pH of the reaction system is adjusted to 5-12. The vacuum drying is performed at 40-50° C. for 20-25 hours.
[0009] The synthesis mechanism of the present invention is as follows: the red peony root extract contains flavonoids such as red paeony glycoside, paeoniflorin, red paeony red and paeoniflorin, as well as terpenoid compounds, and contains a small amount of saponins, phenolic acid, red peony polysaccharide and other compounds. Among them, the compounds such as flavonoids, terpenes, saponins and phenolic acid contain abundant functional groups such as hydroxyl and carboxyl groups, which are combined with metal ions through chelation, and reduced under hydrothermal conditions to obtain single copper. The copper crystal nucleus with high surface activity is combined with the attapulgite rod crystal with rich hydroxyl surface, and at the same time, the product after the oxidation of the biomolecule and the biomolecules such as polysaccharide are combined with the copper-based nanoparticles with high surface activity, and finally the attapulgite nanocomposite material loaded with small-sized copper-based nanoparticles is obtained.
[0010] Figure 1 and Figure 2 These are the XRD spectrum and TEM images of the copper-based nanoparticle / attapulgite composite antibacterial material prepared in Example 2 of the present invention. Figure 1 The diffraction peak of zero-valent copper appears in the solution, indicating that the attapulgite nanocomposite antibacterial material loaded with pure copper nanoparticles is obtained at a pH of 5. Figure 2 The copper nanoparticles are shown to be spherical structures of 2 to 5 nm, with uniform particle sizes, and are uniformly loaded on the surface of attapulgite rod crystals.
[0011] Figure 3 and Figure 4 XRD spectrum and TEM image of the copper-based nanoparticle / attapulgite composite antibacterial material prepared in Example 4 of the present invention. Figure 3 The diffraction peak of cuprous oxide appeared in the solution, indicating that the cuprous oxide nanoparticle-loaded attapulgite nanocomposite antibacterial material was obtained at a pH of 10; the TEM image showed that evenly distributed cuprous oxide nanoparticles were formed on the surface of the attapulgite rod crystals, and the particle size was about 2~3nm.
[0012] Figure 5 The pure cuprous oxide nanoparticles prepared by the same method as in Example 4 of the present invention have serious particle agglomeration and are relatively large in size. The above results show that the attapulgite nanocomposite material loaded with copper-based nanoparticles was successfully prepared by a hydrothermal method using red peony root extract, and the attapulgite played a good role in dispersing and stabilizing the nanoparticles, thereby obtaining copper-based nanoparticles with small particle size.
[0013] 2. Antibacterial properties of copper-based nanoparticles / attapulgite composite antibacterial materials The antibacterial properties of the copper-based nanoparticle / attapulgite composite antibacterial material prepared in the embodiment of the present invention are shown in Figure 2, which shows that the antibacterial properties of the copper-based nanoparticle / attapulgite composite antibacterial material are resistant to methicillin-resistant Staphylococcus aureus (MRSA) and extended-spectrum β-lactamase-producing Escherichia coli (ESBLs- E. coli ) was used as the test strain, and the minimum inhibitory concentration (MIC) was evaluated by the microbroth dilution method. The test method was as follows: 1) Preparation of the test bacteria: Use an inoculation loop to pick a single colony on the MH agar plate cultured overnight at 37°C and place it in MH broth medium. Prepare a 0.5 McFarland turbidity standard (10 8 CFU / mL) of bacterial suspension was diluted to 10 with MH broth. 6 CFU / mL; 2) Prepare 4 mg / mL sample suspension, take 0.2 mL and add it to the first well of a 96-well plate, add 0.1 mL MH broth medium to the second to seventh wells of the 96-well plate, then draw 0.1 mg / mL from the first well and add it to the following wells, add 0.1 mg / mL bacterial suspension to each well after dilution, at this time, the volume of each well is 0.2 mL, and the drug concentrations in the first to seventh wells are 2, 1, 0.5, 0.25, 0.125, 0.0625, and 0.03125 mg / mL, respectively. Add 0.1 mL of bacterial suspension to 0.1 mL MH broth as a positive control group. The above experiment was repeated in three groups. The minimum drug concentration that completely inhibits bacterial growth in the small well is MIC. The antibacterial performance evaluation results of the copper-based nanoparticle / attapulgite composite antibacterial material in Examples 1-6 are shown in Table 1, which shows that the copper-based nanoparticle / attapulgite composite antibacterial material prepared by the present invention is effective against drug-resistant bacteria MRSA and ESBLs- E. coli It has good antibacterial activity.
[0014] The visible light catalytic antibacterial performance of the copper-based nanoparticle / attapulgite composite antibacterial material prepared in the embodiment was evaluated by the following method: first, different concentrations of sample solution (20, 10, 5, 2.5, 1.25, 0.625, 0.3125 mg / mL) were prepared by multiple dilution method, 0.08 mL of bacterial suspension was added to the small wells of 96 microplates, 0.01 mL of the sample dispersion to be tested was added, and 0.01 mL of hydrogen peroxide was added to each well, and lightly beaten to mix; a 40W incandescent lamp was used as the light source to simulate visible light, and the samples were irradiated at 220 rpm and 37°C for 1 hour in a constant temperature shaker, and then placed in a constant temperature incubator at 37°C for 16-18 hours, and the DO value was tested with an enzyme marker. The sample group with hydrogen peroxide added but not irradiated was set as the control group, and all experiments were set up with three replicates.
[0015] The evaluation results of the visible light catalytic antibacterial performance of the attapulgite-copper-based nanocomposite antibacterial materials in Examples 4-6 are shown in Table 2, which shows that the attapulgite-copper-based nanocomposite antibacterial materials prepared by the present invention have obvious photocatalytic antibacterial activity, and compared with the nanocomposite antibacterial materials without light treatment, the visible light catalytic antibacterial performance of the attapulgite-copper-based nanocomposite antibacterial materials is better than that of the nanocomposite antibacterial materials without light treatment. E. coli The antibacterial activity was significantly enhanced.
[0016] The photothermal antibacterial performance of the copper-based nanoparticle / attapulgite composite antibacterial material prepared in the embodiment was evaluated by the following method: a 4 mg / mL sample suspension was prepared, 0.2 mL was added to the first well of a 96-well plate, 0.1 mL of MH broth medium was added to the second to seventh wells of the 96-well plate, and then 0.1 mg / mL was drawn from the first well and added to the subsequent wells, and 0.1 mg / mL of bacterial suspension was added to each well after dilution, and gently tapped to mix; at this time, the volume of each well was 0.2 mL, and the drug concentrations in the first to seventh wells were 2, 1, 0.5, 0.25, 0.125, 0.0625, and 0.03125 mg / mL, respectively. Then infrared light (808 nm, 2.5 W cm -1 ) for 5 min, incubate in a constant temperature incubator at 37°C for 16-18 h, and measure DO value with an ELISA reader. All experiments were repeated three times.
[0017] The photothermal antibacterial performance evaluation results of the copper-based nanoparticle / attapulgite composite antibacterial materials in Examples 1-6 are shown in Table 3, which shows that the copper-based nanoparticle / attapulgite composite antibacterial materials prepared by the present invention have obvious photothermal antibacterial activity, and compared with the copper-based nanoparticle / attapulgite composite antibacterial materials not subjected to light treatment, the photothermal antibacterial activity is better than that of the copper-based nanoparticle / attapulgite composite antibacterial materials against drug-resistant bacteria MRSA and ESBLs- E. coli The antibacterial activity of the catalyst was significantly enhanced and was superior to that of the photocatalytic catalyst.
[0018] The cytotoxicity of the copper-based nanoparticle / attapulgite composite antibacterial materials prepared in Example 2 and Example 4 was evaluated by CKK-8 method. Mouse embryonic fibroblasts (NIH-3T3) in the exponential growth phase were cultured in 96-well plates at 5×10 4 After incubation of cells / well in 100 µL complete medium for 24 h, the medium was replaced with complete medium containing different concentrations of nanocomposites. After further incubation for 24 h, the medium containing different concentrations of nanocomposites was replaced with 100 µL complete medium containing 10% CCK-8 reagent, and then the absorbance at 460 nm was measured using a multi-function microplate reader, and the cell viability was calculated. The blank control group was replaced with fresh complete medium without nanocomposites instead of old medium. Each group of experiments was performed in parallel three times. The experimental results are shown in Figure 2. Figure 6 As shown, it can be found that the cell survival rates of the copper nanoparticle / attapulgite composite antibacterial material and the cuprous oxide nanoparticle / attapulgite composite antibacterial material prepared in Example 2 and Example 4 were maintained above 90% when the concentration was less than 2.5 mg / mL, and the cell survival rate decreased slightly after the concentration increased but was still not less than 80%, indicating that the copper-based nanoparticle / attapulgite composite antibacterial material prepared by the present invention has low cytotoxicity and high safety.
[0019] In summary, the copper-based nanoparticle / attapulgite composite antibacterial material prepared by using red peony root extract in the present invention has the following advantages: 1. Red peony root extract is used to replace chemical reducing agents and stabilizers, which is clean and environmentally friendly. The obtained nanocomposite materials are green and safe, and conform to the green chemical production concept.
[0020] 2. Attapulgite nanorod crystals promote heterogeneous nucleation of nanoparticles through hydrogen bonding, prevent particle agglomeration, and stabilize nanoparticles.
[0021] 3. By regulating the pH of the reaction system, attapulgite-based antibacterial materials loaded with copper and cuprous oxide nanoparticles can be obtained. They have excellent photocatalytic antibacterial and photothermal antibacterial activities and show strong bactericidal ability against resistant bacteria. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the XRD spectrum of the copper-based nanoparticle / attapulgite composite antibacterial material prepared in Example 2 of the present invention; Figure 2 This is a TEM spectrum image of the copper-based nanoparticle / attapulgite composite antibacterial material prepared in Example 2 of the present invention; Figure 3 This is the XRD spectrum of the copper-based nanoparticle / attapulgite composite antibacterial material prepared in Example 4 of the present invention; Figure 4 This is a TEM spectrum image of the copper-based nanoparticle / attapulgite composite antibacterial material prepared in Example 4 of the present invention; Figure 5 This is a TEM image of pure cuprous oxide nanoparticles prepared in Example 4 of the present invention; Figure 6 These are the cytotoxicity evaluation results of the copper-based nanoparticle / attapulgite composite antibacterial materials prepared in Examples 2 and 4. DETAILED DESCRIPTION
[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.
[0024] Example 1 5 g of red peony root was crushed and passed through a 200-mesh sieve, then added into 90 mL of deionized water. After soaking overnight, the mixture was extracted in a water bath at 50°C for 2 h, and centrifuged to obtain a red peony root extract. Under stirring conditions, 1 g of attapulgite was dispersed in 80 mL of red peony root extract to obtain a attapulgite suspension. 1 g of copper acetate monohydrate was added and stirred at room temperature for 3 h. The pH was adjusted to 6 with 1 mol / L sodium hydroxide and then poured into a reactor. The mixture was placed in an oven at 120°C for 4 h. The product was centrifuged, washed three times with deionized water, and dried in vacuo at 45°C for 24 h to obtain a copper-based nanoparticle / attapulgite composite antibacterial material.
[0025] Example 2 10g of red peony root was crushed through 200 mesh and added into 90mL of deionized water. After soaking overnight, the mixture was ultrasonically extracted at 60°C for 1h and centrifuged to obtain a red peony root extract. Under stirring conditions, 2g of attapulgite was dispersed in 70mL of red peony root extract to obtain a attapulgite suspension. 1.6g of copper acetate monohydrate was added and stirred at room temperature for 4h. The pH was adjusted to 5 with 0.5mol / L sodium hydroxide and then poured into a reactor. The mixture was placed in an oven at 100°C for reaction for 6h. The product was centrifuged, washed three times with deionized water, and dried in vacuo at 45°C for 24h to obtain a copper-based nanoparticle / attapulgite composite antibacterial material.
[0026] Example 3 3 g of red peony root was crushed through 200 mesh and added into 90 mL of deionized water. After soaking overnight, the mixture was ultrasonically extracted at 70°C for 0.5 h and centrifuged to obtain a red peony root extract. Under stirring conditions, 0.5 g of attapulgite was dispersed in 50 mL of red peony root extract to obtain a attapulgite suspension. After adding 0.2 g of copper nitrate trihydrate and stirring at room temperature for 2 h, the pH was adjusted to 7 with 2 mol / L sodium hydroxide and then poured into a reactor. The mixture was placed in an oven at 80°C for reaction for 10 h. The product was centrifuged, washed three times with deionized water, and dried in vacuo at 45°C for 24 h to obtain a copper-based nanoparticle / attapulgite composite antibacterial material.
[0027] Embodiment 4: 15g of red peony root was crushed through 200 mesh and added into 90mL of deionized water. After soaking overnight, the mixture was ultrasonically extracted at 60°C for 1h and centrifuged to obtain a red peony root extract. Under stirring, 2g of attapulgite was dispersed in 75mL of red peony root extract to obtain a attapulgite suspension. 2g of copper nitrate trihydrate was added and stirred at room temperature for 5h. The pH was adjusted to 10 with 4mol / L sodium hydroxide and then poured into a reactor. The mixture was placed in an oven at 150°C for reaction for 2h. The product was centrifuged, washed three times with deionized water, and dried in vacuo at 45°C for 24h to obtain a copper-based nanoparticle / attapulgite composite antibacterial material.
[0028] Example 5 30g of red peony root was crushed through 200 mesh and added into 90mL of deionized water. After soaking overnight, the mixture was ultrasonically extracted at 70°C for 0.5h and centrifuged to obtain a red peony root extract. Under stirring, 5g of attapulgite was dispersed in 80mL of red peony root extract to obtain a attapulgite suspension. 10.8g of cupric chloride was added and stirred at room temperature for 4h. The pH was adjusted to 9 with 3mol / L sodium hydroxide and then poured into a reactor. The mixture was placed in an oven at 180°C for reaction for 0.5h. The product was centrifuged, washed three times with deionized water, and dried in vacuo at 45°C for 24h to obtain a copper-based nanoparticle / attapulgite composite antibacterial material.
[0029] Example 6 15g of red peony root was crushed through 200 mesh and added into 90mL of deionized water. After soaking overnight, the mixture was ultrasonically extracted at 55°C for 1.5h and centrifuged to obtain a red peony root extract. Under stirring conditions, 3g of attapulgite was dispersed in 75mL of red peony root extract to obtain a attapulgite suspension. 5g of copper acetate monohydrate was added and stirred at room temperature for 4h. The pH was adjusted to 12 with 5mol / L sodium hydroxide and then poured into a reactor. The mixture was placed in an oven at 100°C for reaction for 6h. The product was centrifuged, washed three times with deionized water, and dried in vacuo at 45°C for 24h to obtain a copper-based nanoparticle / attapulgite composite antibacterial material.
Claims
1. A method for preparing a copper-based nanoparticle / attapulgite composite antibacterial material using a red peony root extract, comprising the steps of: crushing and sieving the red peony root, adding the crushed red peony root into deionized water, soaking the mixture in a water bath at 50-70° C. for extraction for 0.5-2 h, and centrifuging to obtain a red peony root extract; dispersing the attapulgite in the red peony root extract under stirring conditions, adding a copper salt and stirring at room temperature for 2-5 h, adjusting the pH value, transferring the mixture into a reactor, performing a hydrothermal reaction at 80-180° C. for 0.5-10 h, naturally cooling the mixture, centrifuging the product, washing it three times with deionized water, and vacuum drying the product to obtain a copper-based nanoparticle-attapulgite nanocomposite antibacterial material.
2. The method for preparing copper-based nanoparticle / attapulgite composite antibacterial material using red peony root extract according to claim 1, characterized in that: The solid-to-liquid ratio of the red peony root to the deionized water is 1:3-1:
30.
3. The method for preparing copper-based nanoparticle / attapulgite composite antibacterial material using red peony root extract according to claim 1, characterized in that: The solid-to-liquid ratio of the attapulgite to the red peony root extract is 1:10-1:
100.
4. The method for preparing copper-based nanoparticle / attapulgite composite antibacterial material using red peony root extract according to claim 1, characterized in that: The copper salt is at least one of copper acetate, copper nitrate and copper chloride, and the copper ion concentration in the reaction system is 0.01-1 mol / L.
5. The method for preparing copper-based nanoparticle / attapulgite composite antibacterial material using red peony root extract according to claim 1, characterized in that: The pH regulator is 0.5-5 mol / L sodium hydroxide, and the pH of the reaction system is adjusted to 5-12.
6. The method for preparing copper-based nanoparticle / attapulgite composite antibacterial material using red peony root extract according to claim 1, characterized in that: Vacuum drying is performed at 40-50°C for 20-25 hours.
Citation Information
Cited By
Supported Cu < + > bactericidal material as well as preparation method and application thereof
CN119744853A
